Prucalopride in Gastroparesis: A Randomized Placebo-Controlled Crossover Study. (August 2019) - Carbone, Florencia; Van den Houte, Karen; Clevers, Egbert; Andrews, Christopher N.; Papathanasopoulos, Athanassos; Holvoet, Lieselot; Van Oudenhove, Lukas; Caenepeel, Philip; Arts, Joris; Vanuytsel, Tim; Tack, Jan
Abstract : OBJECTIVES: Prokinetics are considered the preferred treatment option for gastroparesis, but evidence of their efficacy is scarce. Prucalopride, a selective 5-hydroxytryptamine 4 receptor agonist used in the treatment of constipation, is able to enhance the gastric emptying rate. In a double-blind, randomized, placebo-controlled crossover study, we evaluated the efficacy of prucalopride to improve the gastric emptying rate and symptoms in patients with gastroparesis. METHODS: Thirty-four patients with gastroparesis (28 idiopathic, 7 men, mean age 42 ± 13 years) were evaluated in a double-blind crossover trial of 4-week treatment periods with placebo or prucalopride 2 mg q.d., separated by 2 weeks of washout. The primary end point was the change in symptom severity, assessed by the Gastroparesis Cardinal Symptom Index; secondary end points comprised the Patient Assessment of Upper Gastrointestinal Disorders–Symptom Severity Index, the Patient Assessment of Upper Gastrointestinal Disorders–Quality of Life, and daily diaries, and the gastric emptying rate was assessed by the 13 C-octanoic acid breath test. RESULTS: Three patients were lost to follow-up. One serious adverse event occurred (small bowel volvulus in the prucalopride group), and 3 patients dropped out because of adverse events of nausea and headache (all prucalopride). For the entire patient group, compared with placebo, prucalopride significantly improved the total Gastroparesis Cardinal Symptom Index (1.65 ± 0.19 vs 2.28 ± 0.20, P < 0.0001) and the subscales of fullness/satiety, nausea/vomiting, and bloating/distention. Prucalopride significantly improved the overall Patient Assessment of Upper Gastrointestinal Disorders–Quality of Life score (1.15 ± 0.16 vs 1.44 ± 0.16, P < 0.05) and the domains of clothing and diet. The gastric half emptying time was significantly enhanced by prucalopride compared with placebo and baseline (98 ± 10 vs 143 ± 11 and 126 ± 13 minutes, P = 0.005 and <0.001, respectively). These significant improvements were also found when considering only the idiopathic gastroparesis subgroup. DISCUSSION: In a cohort of patients with predominantly idiopathic gastroparesis, 4 weeks of prucalopride treatment significantly improved symptoms and quality of life and enhanced gastric emptying compared with placebo.